Catalytic Effect of Cesium Cation Adduct Formation on the Decarboxylation of Carboxylate Ions in the Gas Phase. Issue 3 (11th December 2013) - Mayeux, Charly; Massi, Lionel; Gal, Jean‐François; Charles, Laurence; Burk, Peeter
Abstract The effect of Cs+ ligation on the decarboxylation of malonic acids (unsubstituted and methyl‐, dimethyl‐, ethyl‐, and phenyl‐substituted) in their carboxylate form was studied in the gas phase using tandem mass spectrometry. The study is based on the comparison of the decarboxylation of the bare monoanion (hydrogen malonates) and of the cesium adduct of the cesium salt (Cs+[cesium hydrogen malonates]) under collisional activation. Energy‐resolved dissociation curves of the negative and positive ions exhibit major differences. Decarboxylation of the cationic adducts of substituted malonic acid salts occurs at significantly lower collisional activation than for the corresponding bare hydrogen malonate anions. The conclusions from these experiments are supported by DFT calculations. The calculated activation parameters (enthalpy and Gibbs energy) confirm that the cesium cation coordination assists the decarboxylation of the carboxylate form.